(untitled) (Anclajes, 2017)
This article focuses on a debate held between liberal Colombian poet Agripina Samper de Ancízar (1831-1894) and the influential conservative writer José María Vergara y Vergara (1831-1872) regarding George Sand in the Bogota press in 1871. Agripina Samper, under her pseudonym Pía Rigán, had a visible presence in the Colombian press, especially in the 1860s, but her work is still being located and studied. Vergara, on the other hand, is perhaps the most influential scholar of the cultural and literary scene at that time. In this study I attempt to show that in this debate, started as a defense of George Sand by the Colombian poet in response to Vergara’s attacks, Rigán keenly identifies and challenges three vital aspects of the conservative project: the attention given to the female body, to language, and to literature. Vergara replies with the violent stance of one who, following Michel Foucault, has the authority to discipline and punish. The context of the debate is on the beginning of the Regeneration in Colombia, an ultraconservative political movement that includes the perpetual infantilization of women, monitoring of the nation’s writings, and the founding of the Colombian Academy of Language as a Hispanizing and moralizing enterprise.